Resolving Solubility Problems and Providing an Overview of Excipients to Boost Oral Drug Bioavailability - Mude, Gaurav (Asian Journal of Pharmaceutics (AJP), 2023)
In this study, the methods and resources to improve the bioavailability and solubility of poorly soluble medications are covered. Common supports that may function as solubilizers, disintegrants, and binders in tablet formulations include hydroxypropyl cellulose (HPC) and starch. It has been shown that HPC increases the solubility and rate of drug dissolution for medications such as caffeine and itraconazole. HPC is soluble in water and polar organic solvents. When combined with other components, it may be used as a binder, solvent, or partly preformed corn starch to assist in making poorly soluble medications more soluble and bioavailable. In most countries, the use of Starch 1500 and microcrystalline cellulose has led to commercial success in new automotive generic and over-thecounter market categories. Decreased reliability offer moisture action, which is crucial for coatings and packing films. The study states that these procedures and the use of excipients may be useful means of resolving solubility issues and enhancing oral medication bioavailability.